(untitled) (Research, Society and Development, 2021)
Among the management support tools, the information system has occupied a prominent place in organizations, with the synchronization of data and information automatically and in real time, relevant within this context. Given this, the objective of this investigation is to identify the implications arising from the lack of communication between the Enterprise Resource Planning (ERP), responsible for supporting Production Planning and Control (PCP) and the Production Management System (SGP), in a metalworking company. To carry out the work, a case study was carried out, with an exploratory and descriptive approach. The results indicate that the lack of communication between systems leads to a reduction in the equipment availability index by 2.11%. Considering the waste due to ordering, plus costs with machine hour and man hour, it is estimated that the value that the company fails to collect borders the R 14,000.00 per year in the analyzed equipment.